SAT0286 Paediatric Vasculitis Damage Index: A New Tool for Standardised Disease Assessment. (10th June 2014) - Dolezalova, P.; Wilkinson, N.; Brogan, P.A.; Anton, J.; Benseler, S.M.; Brunner, J.; Cabral, D.A.; Cimaz, R.; O'Neil, K.M.; Özen, S.; Luqmani, R.
Abstract : Background: Standardised assessment of disease damage is one of the main components of the OMERACT core set of outcome measures in adult ANCA-associated vasculitis. There is no validated tool to assess disease damage in children with vasculitis. While paediatric vasculitis shares many features with adult disease scoring tools validated for use in adults may miss some childhood specific damage. The Paediatric Vasculitis Outcome working group gathers physicians interested in childhood vasculitis from the PReS Vasculitis Working Group and the North American CARRA Vasculitis Committee. In collaboration with EUVAS, adaptation of adult vasculitis assessment tools was considered appropriate for paediatric disease. Vasculitis damage tool development followed our publication of the Paediatric Vasculitis Activity Score (PVAS). 1 Objectives: To develop a paediatric modification of the Vasculitis Damage Index (VDI). 2 Methods: Invited paediatric specialists and the group members reviewed existing items of the VDI and some additional items. Using nominal group technique consensus was obtained on damage items and their definitions for use in a paediatric modification of VDI (PVDI). Feasibility, face and content validity were assessed by paper case evaluations. Results: Vasculitis damage is defined as the presence of irreversible features present for at least 3 months since the onset of vasculitis. While the VDI is an inventory of 64 items grouped into 11 organ systems, PVDI contains 72 items in 10 systems: musculoskeletal, skin/mucous membranes, ocular, ENT, chest, cardiovascular, abdominal, renal, nervous and "other". A detailed PVDI glossary was produced. A separate assessment of school absence was added to the one-page form. Each item can be scored as "present" or "no longer present"(NLP), in order to address the potential reversibility of items that fulfil the definition of damage by duration and psychosocial impact but may completely resolve (e.g. growth delay). Every scored item always receives only one point, whether scored "present" or "NLP", in order to retain compatibility with the VDI. Conclusions: PVDI development is an important step towards better disease assessment in children which together with the PVAS allows paediatric vasculitis clinical trials and collaborative studies to gather reliable data on these rare diseases. The PVDI has yet to complete the validation process by its prospective use in real patients, which is currently underway. We aim to ensure that it remains a dynamic data-driven tool reflecting ongoing developments in the field of adult vasculitis damage assessment. References: Dolezalova P, Price-Kuehne FE, Özen S et al. Disease activity assessment in childhood vasculitis: development and preliminary validation of the Paediatric Vasculitis Activity Score (PVAS). Ann Rheum Dis 2013 Oct;72(10):1628-33. Exley AR, Bacon PA, Luqmani RA, et al. Development and initial validation of the Vasculitis Damage Index (VDI) for the standardised clinical assessment of damage in the systemic vasculitides. Arthritis Rheum 1997;40:371-80 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5893